Assessment of Canopy Conductance Responses to Vapor Pressure Deficit in Eight Hazelnut Orchards Across Continents - Pasqualotto, Gaia; Carraro, Vinicio; Suarez Huerta, Eloy; Anfodillo, Tommaso (Frontiers in Plant Science, 2021)
A remarkable increase in vapor pressure deficit (VPD) has been recorded in the last decades in relation to global warming. Higher VPD generally leads to stomatal closure and limitations to leaf carbon uptake. Assessing tree conductance responses to VPD is a key step for modelling plant performances and productivity under future environmental conditions especially when trees are cultivated well outside their native range as it is for hazelnut (Corylus spp.). Our main aim is to assess the stand-level surface canopy conductance (Gsurf) responses to VPD in hazelnut across different continents for providing a proxy of the potential productivity. Tree sap flow (Fd) was measured by TDP probes (6 per site) in 8 orchards of hazelnut in France, Italy, Georgia, Australia and Chile during three growing seasons since 2016 together with the main meteorological parameters. We extracted diurnal Fd to estimate the canopy conductance Gsurf.. In all sites, the maximum of Gsurf occurred at low values of VPD (on average 0.57 kPa) showing that hazelnut promptly avoids leaf dehydration, and that maximum leaf gas exchange is limited at relatively low VPD (i.e. often less than 1 kPa). The sensitivity of the conductance vs. VPD (i.e. -dG/dlnVPD) resulted much lower (average m = -0.36) compared to other tree species, with little differences among sites. We identified a range of sub-optimal VPD conditions for Gsurf maximization (Gsurf > 80% compared to maximum) in each site, named “VPD80”, which multiplied for the mean Gsurf might be used as a proxy for assessing the maximum gas exchange of the orchard under a specific management and site. The potential gas exchange appeared relatively constant in most of the sites except in France (much higher) and in the driest Australian site (much lower). This work assessed the sensitivity of hazelnut to VPD and proposed a simple proxy for predicting the potential gas exchange in different areas. Our results can be used for defining suitability maps based on average VPD conditions thus facilitating the correct identification of the potentially most productive sites.